2011
DOI: 10.1007/s11999-010-1575-2
|View full text |Cite
|
Sign up to set email alerts
|

Does Smoking Influence Fusion Rates in Posterior Cervical Arthrodesis With Lateral Mass Instrumentation?

Abstract: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
1
36
0
2
Order By: Relevance
“…However, in the present study, smoking status was not found to be an independent factor strong enough to modify the proposed score. This fact may be related to the relatively high smoking rate in the population under analysis (68.9 %), which differs from the epidemiological characteristics of other previous series [21,36]. In fact, as already mentioned, although no influence was found between smoking status and surgical outcomes in the sample as a whole, a non-statistically significant difference was found between smoking status and the borderline group LUFOS 2.…”
Section: Discussionmentioning
confidence: 59%
“…However, in the present study, smoking status was not found to be an independent factor strong enough to modify the proposed score. This fact may be related to the relatively high smoking rate in the population under analysis (68.9 %), which differs from the epidemiological characteristics of other previous series [21,36]. In fact, as already mentioned, although no influence was found between smoking status and surgical outcomes in the sample as a whole, a non-statistically significant difference was found between smoking status and the borderline group LUFOS 2.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, our study can fill this gap. Because this was a randomized, double-blind, placebo-controlled trial, we can easily avoid the potential analytical interference by some confounders such as BMD, BMI, smoking or NSAID use [6,7,17].…”
Section: Discussionmentioning
confidence: 99%
“…5 The impact of smoking status on spine surgery has been subject to research, and although studies have shown an association between smoking and poor bone quality 6 and higher rates of pseudarthrosis, 7 , 8 clinical studies have shown confl icting results. [9][10][11][12][13] On the contrary, few studies have assessed the relationship between smoking and perioperative complications after spine surgery, and results have also been inconsistent. 14 , 15 The purpose of this study is to examine the impact of smoking status on both postoperative complications and pseudarthrosis, in adult patients undergoing single-and 2-level instrumented posterolateral fusions (PLFs) of the lumbar spine.…”
mentioning
confidence: 99%